Laparoscopic versus open appendectomy: a prospective comparative study - Pradhan, Sumita; Shakya, Yagya Ratna; Batajoo, Hemant; Malla, Balram; Joshi, Hem Nath; Thapa, Lok Bikram; Makaju, Ram Kantha (Journal of Society of Surgeons of Nepal, 2017)
Introduction: Appendectomy is one of the most commonly performed surgeries usually done by conventional open method. The role of laparoscopic appendectomy is still not well defined in the literature and although widely practiced it still hasn’t gained popularity in Nepal. The aim of this study was to compare the outcomes of laparoscopic versus open appendectomy. Methods: A prospective study was carried out, between August 2013 and September 2014, involving 216 patients (93 males and 123 females) with a diagnosis of acute appendicitis based on Alvarado score of seven and above. Patients were allocated into two groups where every alternate patient was operated either open or laparoscopically. The groups were compared in terms of operative time, post operative pain, post operative complications and length of hospital stay. Results: Open appendectomy (OA) comprised of 106 patients and Laparoscopic appendectomy (LA) comprised of 110 patients. Patients’ characteristics were similar in both groups. The mean operative time in LA was 42.82±10.84 minutes and in OA 37.99±9.81 minutes (p<0.86). Conversion was done in 2.8% of laparoscopic cases. Mean comparison of postoperative pain by visual analogue scale was low in LA compared to OA (P<0.05). Mean post operative stay (3.19±1.26 vs 2.75±0.7, p<0.01) and surgical site infection was recorded in 9 patients (8.5%) in OA group and 3 (2.5%) in LA group, with p value of 0.06. Conclusions: Laparoscopic appendectomy is feasible and safe as open procedure with less post operative pain and shorter hospital stay. Journal of Society of Surgeons of Nepal, 2015; 18 (2), page: 29-32